PEMBINAAN PERSONIL KEPOLISIAN DALAM MENINGKATKAN PELAYANAN MASYARAKAT DI POLSEKTA PELABUHAN SAMARINDA - Novandi Arya Kharizma (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The aim of this study is to describe and analyze the Police Personnel Development to Improve Community Services in Port Samarinda. Analysis of the data used is Flow models developed by Miles and Huberman, and Saldana. From the results of this study concluded that fostering police personnel conducted Polsekta Port of Samarinda managed to improve skills, the skills and expertise of personnel, and in addition to the creation of police personnel who have the ethos of work and changes in attitudes and behaviorel good and has a strong commitment to carry out his duties as a security activities , either in the port area as well as in the waters of the harbor.